Oculomotor apraxia and disrupted sleep with nocturnal ballistic bouts in ADCY5-related disease - Balint, Bettina (Parkinsonism & related disorders, 2018)
Objective - To characterise the distinctive eye movement disorder and the sleep-related dyskinesia in Adenylate cyclase 5 (ADCY5) related disease. - Methods - Formal eye movement examination and video-polysomnography in a cohort of patients with ADCY5 mutations. - Results - All three patients had an eye movement disorder characterised by oculomotor apraxia with gaze limitation most prominently in the vertical plane. All patients had disrupted sleep architecture with reduced sleep efficiency due to frequent and prolonged arousals and awakenings in the context of dyskinesia, which could arise from any sleep stage. The nocturnal movements could last up to 30min and be more severe than those seen during day-time. - Conclusion - Nocturnal exacerbations of dyskinesia (“ballistic bouts”) seem to be a characteristic feature of the disease, affect the quality of life of patients and therefore require awareness and symptomatic treatment approaches. Apraxia of eye movements, with predominant difficulties in the vertical plane, was a common finding in our patients with ADCY5 mutations. These features may prompt the diagnosis and help to distinguish ADCY5-related disease from other childhood-onset hyperkinetic movement disorders.
Gesehen am 04.03.2020